Extra Cellular Endoxylanase Production from Solid State Fermentation of Dried Grass by Streptomyces sp OM 09 - Rani Ray*, Rina (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The present study deals with the cost effective production of endoxylanase by a strain of Streptomyces sp, isolated from soil of Kanha National park and Tiger Reserve, India. Among various agricultural residues used in the solid state fermentation media, grass followed by rice straw proved to be the best carbon source for the growth and production of extracellular endoxylanase by the strain. Drying of the grass improved the enzyme production and best enzyme production was obtained at a concentration of 1%. Highest endoxylanase production was found at pH 6.0 and at 37°C. The kinetics of growth and enzyme production showed that highest enzyme production could be achieved within 48 hours of cultivation. The endoxylanase produced, after partial purification showed highest activity at 60°C and at pH 6.0.The enzyme showed moderate thermostability and stability at a pH range of 5.0- 8.5 and a substrate specificity towards xylan only. The improvement of enzyme activity in presence of thiol compounds indicated the presence of thiol group at the active site of the enzyme.